Restoration of Genetic Code in Macular Mouse Fibroblasts via APOBEC1-Mediated RNA Editing - Sonali Bhakta; Hiroko Kodama; Masakazu Mimaki; Toshifumi Tsukahara (Biomolecules)
RNA editing is a significant mechanism underlying genetic variation and protein molecule alteration; C-to-U RNA editing, specifically, is important in the regulation of mammalian genetic diversity. The ability to define and limit accesses of enzymatic machinery to avoid the modification of unintended targets is key to the success of RNA editing. Identification of the core component of the apoB RNA editing holoenzyme, APOBEC, and investigation into new candidate genes encoding other elements of the complex could reveal further details regarding APOBEC-mediated mRNA editing. Menkes disease is a recessive X-chromosome-linked hereditary syndrome in humans, caused by defective copper metabolism due to mutations in the ATP7A gene, which encodes a copper transport protein. Here, we generated plasmids encoding the MS2 system and the APOBEC1 deaminase domain and used a guide RNA with flanking MS2 sites to restore mutated Atp7a in fibroblasts from a macular mouse model of Menkes disease withs T>C mutation. Around 35% of the mutated C nucleotide (nt) was restored to U, demonstrating that our RNA editing system is reliable and has potential for therapeutic clinical application. RNA base editing via human RNA-guided cytidine deaminases is a potentially attractive approach for in vivo therapeutic application and provides opportunities for new developments in this field.